Study on the cooling effect of the parallel perforated ventilation subgrade in permafrost regions based on the numerical model. - Xiaolan Liu; Chuanwei Fu; Xinglei Cheng (PLoS ONE)
The runway in permafrost regions has remarkable temperature sensitivity. Therefore, this paper puts forward to the parallel perforated ventilation subgrade. The reliability and validity of the finite element model of the runway with the parallel perforated ventilation subgrade are verified by comparing with the previous studies. And the cooling effect of the parallel perforated ventilation subgrade is analyzed. Results show that the parallel perforated ventilation subgrade has a significant cooling effect on the pavement and has little cooling effect in the natural ground. Compared with the non-ventilation subgrade, temperature time-history curves for the parallel perforated ventilation subgrade change periodically each year and are gradually lower with the growth of time. Temperature-depth curves for the parallel perforated ventilation subgrade change significantly at the insulation layer, the crushed rock layer, and the perforated ventilation. The air velocity and working time of the parallel perforated ventilation have no effect on the temperature of the surface layer, base layer, and subbase layer, have little effect on the temperature of the insulation layer, and have great effect on the temperature of the crushed rock layer and subgrade. This study provides scientific support for the design, construction, and maintenance of the runway in permafrost regions.